A novel memristive true random number generator design. Issue 6 (24th July 2019) - Cam Taskiran, Zehra Gulru; Taşkıran, Murat; Kıllıoğlu, Mehmet; Kahraman, Nihan; Sedef, Herman
Abstract : Purpose: In this work, a true random number generator is designed by sampling the double-scroll analog continuous-time chaotic circuit signals. Methodology: A Chua circuit based on memristance simulator is designed to obtain a non-linear term for a chaotic dynamic system. It is implemented on the board by using commercially available integrated circuits and passive elements. A low precision ADC which is commonly found in the market is used to sample the chaotic signals. The mathematical analysis of the chaotic circuit is verified by experimental results. Originality: It is aimed to be one of the pioneering studies (including low precision ADC) in the literature on the implementation of memristive chaotic random number generators. Findings: Two new methods are proposed for post-processing and creating random bit array using XOR operator and J-K flip flop. The bit stream obtained by a full-hardware implementation successfully passed the NIST-800-22 test. In this respect, the availability of the memristance simulator circuit, memristive chaotic double-scroll attractor, proposed random bit algorithm and the randomness of the memristive analog continuous-time chaotic true number generator were also verified.